2022
DOI: 10.3390/toxics10060286
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Safety Evaluation of Black Tea Extract (Herbt Tea Essences) in Mice

Abstract: Theabrownin (TB) is a heterogeneous biomacromolecule, extracted from tea, with many functional groups. Importantly, TB possesses diverse health benefits, such as antitumor activity and blood lipid-lowering effects. Presently, the content of TB in tea extract is relatively low. Here, we obtained a deep-processed black tea extract with a high content of TB (close to 80%), which was named Herbt Tea Essences (HTE). Currently, this study was designed to evaluate the biosafety of high-content TB products on mice. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The LC 50 of potassium dichromate and MCFE was 15.69 and 25.29 µg/ml respectively. Based on the correlation findings as reported by Parra et al, for test substances which showed LC 50 < 10 μg/ml possesses LD 50 between 100 and 1,000 mg/kg; LC 50 < 20 μg/ml possesses LD 50 between 1,000 and 2,500 mg/kg and LC 50 > 25 μg/ml possesses LD 50 between 2,500 and 8,000 mg/kg (Ding et al, 2022). The LC 50 for MCFE was in the range of LC 50 > 25 μg/ml and therefore the LD 50 for MCFE was expected between 2,500 and 8,000 mg/kg.…”
Section: Brine Shrimp Lethality Assaymentioning
confidence: 81%
“…The LC 50 of potassium dichromate and MCFE was 15.69 and 25.29 µg/ml respectively. Based on the correlation findings as reported by Parra et al, for test substances which showed LC 50 < 10 μg/ml possesses LD 50 between 100 and 1,000 mg/kg; LC 50 < 20 μg/ml possesses LD 50 between 1,000 and 2,500 mg/kg and LC 50 > 25 μg/ml possesses LD 50 between 2,500 and 8,000 mg/kg (Ding et al, 2022). The LC 50 for MCFE was in the range of LC 50 > 25 μg/ml and therefore the LD 50 for MCFE was expected between 2,500 and 8,000 mg/kg.…”
Section: Brine Shrimp Lethality Assaymentioning
confidence: 81%
“…Mechanistically, HTE improved lipid and glucose metabolism by activating key signalling pathways and modulating the expression of key genes involved in these two processes. As HTE administration was helpful to improve glucose and lipid metabolism, and HTE consumption has been shown to be safe [39], HTE should be expected to have marketing prospects.…”
Section: Discussionmentioning
confidence: 99%